The impact of T cells on immune-related liver diseases: an overview - Yuzo Koda; Ryosuke Kasuga; Nobuhito Taniki; Takanori Kanai; Nobuhiro Nakamoto (Inflammation and Regeneration)
Abstract The liver presents a unique immune system. Liver diseases are closely associated with the immune system. Disruption of the tightly regulated balance between immune activation and tolerance induction leads to the development and worsening of immune-related liver diseases. T cells play diverse crucial roles in the immune system, and they have long been known to induce inflammation through direct tissue damage by effector molecules and the recruitment of effector cells via chemokines. Additionally, T cells interact with B cells to induce autoantibodies, promoting tissue inflammation and dysfunction through the deposition of IgG and immune complexes in the tissues. Recent advances in omics technologies, including single-cell RNA sequencing and spatial transcriptomics, have elucidated the role of T cells in the progression and recovery of liver fibrosis. Moreover, comprehensive and unbiased information can now be obtained from small samples of human and mouse tissues, which advances our understanding of tissue-specific functions of T cells, including resident memory T cells, peripheral helper T cells, and tissue Tregs. However, significant unmet needs remain in the fields of immune-related liver diseases. In this review, we discuss the T cell biology and its role in autoimmune hepatitis (AIH), primary sclerosing cholangitis (PSC), primary biliary cholangitis (PBC), and metabolic-associated steatohepatitis (MASH), which are non-viral liver diseases exhibiting a strong involvement of immunity and inflammation. Furthermore, the latest therapeutic concepts for the diseases and associated drugs targeting T cells have been overviewed.